2020
DOI: 10.14336/ad.2020.0217
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Metabolic Profile and Potential Biomarkers in the Plasma of Alzheimer’s Disease

Abstract: The expending of elderly population worldwide has resulted in a dramatic rise in the incidence of chronic diseases such as Alzheimer's disease (AD). Inadequate understanding of the mechanisms underlying AD has hampered the development of efficient tools for definitive diagnosis and curative interventions. Previous studies have attempted to discover reliable biomarkers of AD, but these biomarkers can only be measured through invasive (neuropathological markers in cerebrospinal fluid) or expensive (positron emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
(62 reference statements)
1
34
0
Order By: Relevance
“…Dysregulation of several metabolic pathways with changes in plasma metabolites has been associated with and may contribute to AD pathology and impairment. 5 Cholesterol metabolism, fatty acid (FA) metabolism, bile acid synthesis, and amino acid metabolism may be the most associated with AD. Therefore, changes in plasma FAs, bile acids, and amino acids are some of the most apparent alterations reported in previous studies.…”
Section: Metabolitesmentioning
confidence: 99%
See 4 more Smart Citations
“…Dysregulation of several metabolic pathways with changes in plasma metabolites has been associated with and may contribute to AD pathology and impairment. 5 Cholesterol metabolism, fatty acid (FA) metabolism, bile acid synthesis, and amino acid metabolism may be the most associated with AD. Therefore, changes in plasma FAs, bile acids, and amino acids are some of the most apparent alterations reported in previous studies.…”
Section: Metabolitesmentioning
confidence: 99%
“…Therefore, changes in plasma FAs, bile acids, and amino acids are some of the most apparent alterations reported in previous studies. 5,[144][145][146] The reduction in the level of polyunsaturated fatty acids (PUFA), particularly docosahexaenoic acid (DHA), has been associated with cognitive impairment due to AD and may be due to impaired FA metabolism in the liver. 5,147, 148 One study showed that cognitive performance improved with dietary supplementation of DHA in AD patients, which could have been due to neuroprotective properties of PUFAs.…”
Section: Metabolitesmentioning
confidence: 99%
See 3 more Smart Citations